"Personal recovery depends on NA unity": an exploratory study on recovery-supportive elements in Narcotics Anonymous Flanders - Anne Dekkers; Sam Vos; Wouter Vanderplasschen (BMC, 2020)
Abstract Background Mutual aid organizations, such as Narcotics Anonymous (NA), can provide support in substance use disorder (SUD) recovery processes. However, research on NA and its recovery-supportive elements is scarce and perspectives of NA-members remain understudied, in particular outside the US. Therefore, this study aims to gain insight into recovery-supportive elements of NA, as experienced by its members. Methods To explore the perspectives on and experiences with recovery-supportive elements in NA, 11 in-depth interviews with NA-members were conducted in Flanders (Belgium). Interviews were audio-taped, transcribed verbatim and analyzed by using CHIME-D, a personal recovery framework (Connectedness, Hope, Identity, Meaning in life, Empowerment, Difficulties) developed by Leamy and colleagues in 2011. Results Various recovery-supportive elements of NA were highlighted, with Connectedness as a key component including opportunities for building up a social network and for providing a safety net or sounding board. Elements that enabled Connectedness were 1) a non-judgemental approach, and 2) mutual understanding through sharing in NA. Other elements of the CHIME-D framework were less frequently mentioned, although these were inextricably linked to Connectedness. Conclusions Connectedness appeared to be the crucial recovery-supportive element in NA, emphasizing the relational character of SUD recovery. Although other elements of the CHIME-D framework were identified, these were closely related to and intertwined with the concept of connectedness.